2004
DOI: 10.1158/1078-0432.ccr-031206
|View full text |Cite
|
Sign up to set email alerts
|

Nonendocrine Pathways and Endocrine Resistance

Abstract: An increasing body of evidence demonstrates that growth factor networks are highly interactive with estrogen receptor signaling in the control of breast cancer growth. As such, tumor responses to antiestrogens are likely to be a composite of the estrogen receptor and growth factor-inhibitory activity of these agents, with alterations/aberrations in growth factor signaling providing a mechanism for the development of antiestrogen resistance. In this light, the current article focuses on illustrating the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
105
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 73 publications
6
105
0
1
Order By: Relevance
“…Previous studies in breast cancer cell lines have in fact implicated HER1/HER2 signaling in lowering the expression of PgR and/or ER [29][30][31]. In particular, in the subgroup of patients with ER positive and PgR absent disease, hyperactive cross-talk between ER and growth factor signaling pathways, leading to a more aggressive course of the disease, was recently reported [32,33]. Previous studies [34,35] conducted also in the preoperative setting [36], found a correlation between the degree of expression of ER and PgR and HER1/HER2 expression, clearly indicating the higher prevalence of endocrine non responsive disease in the group of patients selected by HER1 and HER2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in breast cancer cell lines have in fact implicated HER1/HER2 signaling in lowering the expression of PgR and/or ER [29][30][31]. In particular, in the subgroup of patients with ER positive and PgR absent disease, hyperactive cross-talk between ER and growth factor signaling pathways, leading to a more aggressive course of the disease, was recently reported [32,33]. Previous studies [34,35] conducted also in the preoperative setting [36], found a correlation between the degree of expression of ER and PgR and HER1/HER2 expression, clearly indicating the higher prevalence of endocrine non responsive disease in the group of patients selected by HER1 and HER2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate that tamoxifen does not completely block the action of E2 in some patients due to high levels of E2. Acquired tamoxifen resistance is believed to arise due to increased phosphorylation of the ER by growth factor signalling or due to increased expression of coactivators (Nicholson et al, 2004, Schiff et al, 2004. This means that tamoxifen acts as an agonist after long duration of treatment in some patients, and the question is how the resistant tumour cells will respond to high E2 levels after the completion of tamoxifen treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence to suggest that growth factor signalling pathways, their downstream effectors and regulators are central to the development of endocrine resistance (Cui et al, 2006). Studies have found that cells with significantly increased levels of MAP kinase associate with resistance to endocrine manipulation (Hutcheson et al, 2003;Nicholson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%